FEATURES OF FORMATION OF CRITICAL THINKING OF PRIMARY CLASS STUDENTS WHEN STUDYING THE DISCIPLINE “EDUCATION” - Erkaboeva Nigora Shermatovna; Elmuratova Odina Elbek qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article is aimed at developing the critical thinking of primary school students in the process of teaching the science of education, which provides the characteristics of the science of education, teaching methods, forms and principles that must be followed.